Nitrogen-doped carbon spheres, and preparation method and application thereof
Patent Information
- Application Number
- CN202311615030.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-28
- Publication Date
- 2026-11-03
- Estimated Expiration
- 2043-11-28
AI Technical Summary
Existing sodium-ion battery anode material, hard carbon, suffers from low sodium storage capacity, poor rate performance, and unstable cycle performance, making it difficult to meet practical requirements. In particular, the large sodium ion radius and small interlayer spacing result in slow kinetics, and the micron-sized structure causes sodium ion transport distance to be large and electrochemical polarization to be severe.
Nitrogen-doped carbon nanospheres were prepared by using dopamine hydrochloride as a carbon and nitrogen source through polymerization and high-temperature heat treatment. This process expanded the carbon lattice spacing, increased the material defect concentration and electronegativity, and constructed a nanosphere structure to shorten the electron/ion transport distance.
The prepared nitrogen-doped carbon spheres have wide carbon interlayer spacing, high electronic conductivity and fast sodium ion diffusion kinetics, which significantly improve sodium storage capacity and rate performance, and exhibit excellent electrochemical performance as a negative electrode material for sodium-ion batteries.
Smart Images

Figure CN117613267B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of energy storage materials technology, and in particular to a nitrogen-doped carbon sphere, its preparation method, and its application. Background Technology
[0002] Developing safe, feasible, and low-cost battery energy storage systems is a crucial means of addressing the challenges of utilizing new renewable energy sources. Compared to commercialized lithium-ion batteries, research on novel sodium-ion batteries has received more widespread attention from the academic community. Sodium ions are abundant in the Earth's crust (abundance of 2.64%), widely distributed, and readily available; sodium and lithium belong to the same main group and have similar physicochemical properties (E...). Na+ / Na = -2.70V, E Li+ / Li = -3.04V vs. SHE); Sodium-ion batteries can be produced using existing lithium-ion battery synthesis processes, which can greatly reduce application costs; at the same time, their electrochemical performance (100-130Wh kg) -1 It can be used with lead-acid batteries (170Wh kg) -1 In comparison, sodium-ion battery technology can effectively reduce the cost of large-scale static grid energy storage and is a new type of battery energy storage system with great application potential.
[0003] However, sodium ions have a relatively large ionic radius (Na₂O₃). + =0.102nm, Li + The low lattice size (0.076 nm) makes finding a suitable sodium-intercalated anode challenging. Hard carbon, composed of randomly stacked, bent graphene microcrystals, has relatively large interlayer spacing and sodium ion diffusion gaps, resulting in minimal lattice structure changes during sodium ion diffusion and a relatively stable structure. Hard carbon exhibits a low discharge potential (~0.1 V vs Na). + Sodium-ion batteries (SO4) with sodium (Na+) are promising anode materials for maintaining a high operating voltage window and energy density in full-cell batteries. However, research shows that hard carbon (HCC) generally suffers from low sodium storage capacity, poor rate performance, and unstable cycle performance, making it difficult to meet the practical requirements of sodium-ion batteries. The main reasons are: firstly, the large radius of sodium ions and small interlayer spacing lead to slow kinetics; secondly, the micron-sized structure results in a long transport distance for sodium ions, leading to severe electrochemical polarization; and finally, the limited number of active sites results in low sodium storage capacity. Therefore, increasing the interlayer spacing, reducing the transport distance, and increasing the number of active sites are key to improving the sodium storage capacity, rate performance, and cycle stability of hard carbon (HCC).
[0004] Designing nitrogen-doped nanospheres is an effective way to improve the sodium storage performance of hard carbon anodes. Doping with nitrogen can increase the carbon lattice spacing, improve the defect concentration and electronegativity of the material, thereby effectively increasing the electrochemical performance of hard carbon for sodium storage. Constructing nanosphere structures can increase the specific surface area of hard carbon materials and shorten the electron / ion transport distance, thus significantly improving the sodium storage capacity and rate performance of hard carbon materials. Currently, solvothermal methods, vapor deposition methods, and template methods are commonly used to prepare nitrogen-doped carbon nanospheres. The solvothermal method for preparing carbon spheres utilizes abundant and inexpensive biomass raw materials, and boasts a simple process, high yield, and low cost. The resulting product is rich in functional groups such as hydroxyl, carboxyl, and carbonyl groups, which endow the carbon microspheres with excellent chemical and physical adsorption properties. However, the graphitization degree of the carbon nanospheres prepared by this method is relatively low, often exhibiting poor conductivity. Furthermore, the preparation process requires a high-pressure environment, significantly increasing the cost of large-scale production. Chemical vapor deposition (CVD) produces carbon nanospheres with a well-defined graphitized structure, resulting in excellent electrical, magnetic, and mechanical properties. However, its reaction conditions are harsh, yield is relatively low, and surface functional groups are fewer. Due to raw material limitations and complex preparation processes, the cost is also high. The template method allows for the selection of different templates based on the desired material morphology, making the shape and properties of the product easily controllable. However, the template must be removed, a relatively cumbersome and complex process that can potentially damage the structure and properties of the carbon microspheres, increasing the difficulty of the preparation process. Summary of the Invention
[0005] To address the above problems, this invention aims to provide a nitrogen-doped carbon sphere, its preparation method, and its application.
[0006] The technical solution of the present invention is as follows:
[0007] On the one hand, a method for preparing nitrogen-doped carbon spheres is provided, comprising the following steps:
[0008] S1: Add dopamine hydrochloride to the mixed solvent, stir for time T1, then add deionized water and continue stirring for time T2 until a brown suspension is obtained.
[0009] S2: Centrifuge, wash and dry the suspension to obtain the precursor material;
[0010] S3: The precursor material is subjected to high-temperature heat treatment under an inert atmosphere to obtain the nitrogen-doped carbon spheres.
[0011] Preferably, in step S1, the amount of dopamine hydrochloride used is 0.3–1.5 g, and the amount of the mixed solvent used is 220.5–324 mL.
[0012] Preferably, the mixed solvent comprises 0.5–4 mL ammonia, 70–120 mL ethanol, and 150–200 mL deionized water.
[0013] Preferably, in step S1, the amount of deionized water used is 10-50 mL.
[0014] Preferably, in step S1, the time T1 is 0.5h and the time T2 is 20-40h.
[0015] Preferably, in step S3, the inert atmosphere is argon and / or nitrogen.
[0016] Preferably, in step S3, the high-temperature heat treatment is performed at a temperature of 500–2000°C for 1–5 hours.
[0017] Preferably, in step S3, the heating rate used during high-temperature heat treatment is 2 to 10 °C / min.
[0018] On the other hand, a nitrogen-doped carbon sphere prepared by any one of the above preparation methods is also provided, and its application as a negative electrode material for sodium-ion batteries is also provided.
[0019] The beneficial effects of this invention are:
[0020] This invention uses dopamine hydrochloride as both a carbon and nitrogen source, enabling the polymerization reaction to proceed at room temperature. Compared to traditional carbon sphere preparation methods such as solvothermal methods, vapor deposition methods, and template methods, this method offers lower raw material costs and a simpler, more efficient preparation process. Through polymerization followed by high-temperature heat treatment, uniform nitrogen-doped carbon nanospheres can be obtained, exhibiting wide carbon interlayer spacing, high electronic conductivity, and fast sodium ion diffusion kinetics. When used as a negative electrode material for sodium-ion batteries, these nanospheres demonstrate excellent electrochemical performance. Attached Figure Description
[0021] To more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the drawings used in the description of the embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 The X-ray diffraction (XRD) pattern of the nitrogen-doped carbon sphere material described in Example 1;
[0023] Figure 2 The full X-ray photoelectron spectroscopy (XPS) spectrum of the nitrogen-doped carbon sphere material described in Example 1.
[0024] Figure 3 The X-ray photoelectron spectroscopy (XPS) N 1s spectrum of the nitrogen-doped carbon sphere material described in Example 1.
[0025] Figure 4 The image shown is a scanning electron microscope (SEM) image of the nitrogen-doped carbon sphere material described in Example 1.
[0026] Figure 5 This is a transmission electron microscope (TEM) image of the nitrogen-doped carbon sphere material described in Example 1.
[0027] Figure 6 The nitrogen-doped carbon sphere material described in Example 1 at 50 mAg -1 Cyclic performance diagram at current density;
[0028] Figure 7 The nitrogen-doped carbon sphere material described in Example 1 at 200 mA g -1 Cyclic performance diagram at current density;
[0029] Figure 8 The X-ray diffraction (XRD) pattern of the nitrogen-doped carbon sphere material described in Example 2;
[0030] Figure 9 The image shown is a scanning electron microscope (SEM) image of the nitrogen-doped carbon sphere material described in Example 2.
[0031] Figure 10 This is a transmission electron microscope (SEM) image of the nitrogen-doped carbon sphere material described in Example 2;
[0032] Figure 11 The nitrogen-doped carbon sphere material described in Example 2 at 200 mAg -1 Cyclic performance diagram at current density;
[0033] Figure 12 The image shown is a scanning electron microscope (SEM) image of the nitrogen-doped carbon sphere material described in Example 3.
[0034] Figure 13 The nitrogen-doped carbon sphere material described in Example 3 was subjected to a temperature of 200 mA g. -1 Cyclic performance diagram at current density.
[0035] Figure 14 As a comparative example 1, the nitrogen-doped hard carbon-coated silica spherical composite material was tested at 200 mAg. -1 Cyclic performance diagram at current density.
[0036] Figure 15 For the nitrogen-doped hollow carbon sphere material described in Comparative Example 2, at 200 mAg -1 Cyclic performance diagram at current density. Detailed Implementation
[0037] The present invention will be further described below with reference to the accompanying drawings and embodiments. It should be noted that, unless otherwise specified, the embodiments and technical features described in this application can be combined with each other. It should also be pointed out that, unless otherwise indicated, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains. The terms "comprising" or "including" and similar words used in this invention refer to elements or objects preceding the word that encompass the elements or objects listed following the word and their equivalents, without excluding other elements or objects.
[0038] On one hand, the present invention provides a method for preparing nitrogen-doped carbon spheres, comprising the following steps:
[0039] S1: Add dopamine hydrochloride to the mixed solvent, stir for time T1, then add deionized water and continue stirring for time T2 until a brown suspension is obtained.
[0040] In one specific embodiment, the amount of dopamine hydrochloride used is 0.3–1.5 g, and the amount of the mixed solvent used is 220.5–324 mL. Optionally, the mixed solvent includes 0.5–4 mL of ammonia, 70–120 mL of ethanol, and 150–200 mL of deionized water.
[0041] In one specific embodiment, when adding deionized water after stirring time T1, the amount of deionized water is 10-50 mL. In this embodiment, adding deionized water after stirring time T1, rather than adding all the deionized water to the mixed solvent, allows for a more uniform dispersion of the spherical dopamine polymer.
[0042] In one specific embodiment, the T1 time is 0.5h, and the T2 time is 20 to 40h.
[0043] S2: The suspension solution is centrifuged, washed, and dried to obtain the precursor material.
[0044] S3: The precursor material is subjected to high-temperature heat treatment under an inert atmosphere to obtain the nitrogen-doped carbon spheres.
[0045] In one specific embodiment, the inert atmosphere is argon and / or nitrogen.
[0046] In one specific embodiment, the high-temperature heat treatment is performed at a temperature of 500–2000°C for a time of 1–5 hours. Optionally, the heating rate is 2–10°C / min.
[0047] On the other hand, a nitrogen-doped carbon sphere prepared by any one of the above preparation methods is also provided, and its application as a negative electrode material for sodium-ion batteries is also provided.
[0048] In one specific embodiment, a sodium-ion battery includes a negative electrode, a positive electrode, a separator between the positive and negative electrodes, and an electrolyte, wherein the negative electrode is the nitrogen-doped carbon sphere of the present invention.
[0049] Example 1
[0050] A nitrogen-doped carbon sphere is prepared by the following steps:
[0051] (1) Add 1.0 g of dopamine hydrochloride to a mixed solvent consisting of 1.5 mL ammonia, 80 mL ethanol and 180 mL deionized water. After stirring for 0.5 h, add 20 mL of deionized water and stir vigorously for 30 h to obtain a brown suspension.
[0052] (2) After centrifuging and washing the suspension, the solution is dried under vacuum at 80°C for 12 hours to obtain the precursor material.
[0053] (3) The precursor material is subjected to high-temperature heat treatment in an argon atmosphere. The specific heating program is as follows: the temperature is increased at a rate of 5℃ / min and held at 1100℃ for 2 hours to obtain the nitrogen-doped carbon spheres.
[0054] The nitrogen-doped carbon spheres obtained in this embodiment were tested, and the X-ray diffraction results are as follows: Figure 1 As shown, the X-ray photoelectron spectroscopy analysis results are as follows: Figure 2 and Figure 3 As shown, the scanning electron microscope results are as follows: Figure 4 As shown, the transmission electron microscopy results are as follows: Figure 5 As shown, at 50mAg -1 Cyclic performance test results at current density are as follows Figure 6 As shown, at 200mAg -1 Cyclic performance test results at current density are as follows Figure 7 As shown.
[0055] from Figure 1 It can be seen that the X-ray diffraction curve of the nitrogen-doped carbon sphere described in this embodiment has two broad diffraction peaks at 24° and 43°, corresponding to the (002) and (100) crystal planes of hard carbon, proving that the synthesized carbon sphere is a hard carbon material.
[0056] from Figure 2 As can be seen, the nitrogen-doped carbon spheres described in this embodiment contain three elements: C, O, and N. The presence of N proves that N has been successfully doped into the carbon spheres.
[0057] from Figure 3 It can be seen that the N element in the nitrogen-doped carbon spheres described in this embodiment exists in the form of pyridine nitrogen, pyrrole nitrogen, graphitic nitrogen and nitrogen oxide in the carbon spheres.
[0058] from Figure 4 and Figure 5 As can be seen, the nitrogen-doped carbon spheres described in this embodiment are uniform nano-carbon sphere structures with a diameter of approximately 700 nm.
[0059] from Figure 6 It can be seen that the nitrogen-doped carbon spheres described in this embodiment have a performance of 50 mA g. -1 At a current density of 391.4 mAh g -1 The first-cycle reversible specific capacity is 84.8%, and the first-cycle coulombic efficiency is 84.8%, with a reversible capacity of 433.7 mA hg after 200 cycles. -1 .
[0060] from Figure 7 It can be seen that the nitrogen-doped carbon spheres described in this embodiment have a performance of 200 mA g. -1 At a current density, it still has 361.0 mAh g. -1 The reversible specific capacity and the ability to cycle for more than 650 cycles without any decay indicate that the nitrogen-doped carbon spheres described in this embodiment have excellent sodium storage cycling performance.
[0061] Example 2
[0062] A nitrogen-doped carbon sphere is prepared by the following steps:
[0063] (1) Add 1.0 g of dopamine hydrochloride to a mixed solvent consisting of 4.0 mL ammonia, 80 mL ethanol and 180 mL deionized water, stir for 0.5 h, then add 20 mL of deionized water, stir vigorously for 30 h to obtain a brown suspension.
[0064] (2) After centrifuging and washing the suspension, the solution is dried under vacuum at 80°C for 12 hours to obtain the precursor material.
[0065] (3) The precursor material is subjected to high-temperature heat treatment in an argon atmosphere. The specific heating program is as follows: the temperature is increased at a rate of 5℃ / min and held at 800℃ for 2 hours to obtain the nitrogen-doped carbon spheres.
[0066] The nitrogen-doped carbon spheres obtained in this embodiment were tested, and the X-ray diffraction results are as follows: Figure 8 As shown, the scanning electron microscope results are as follows: Figure 9 As shown, the transmission electron microscopy results are as follows: Figure 10 As shown, at 200mAg -1 Cyclic performance test results at current density are as follows Figure 11 As shown.
[0067] from Figure 8It can be seen that the X-ray diffraction curve of the nitrogen-doped carbon sphere described in this embodiment has two broad diffraction peaks at 24° and 43°, corresponding to the (002) and (100) crystal planes of hard carbon, proving that the synthesized carbon sphere is a hard carbon material.
[0068] from Figure 9 and Figure 10 As can be seen, the nitrogen-doped carbon spheres described in this embodiment are uniform nano-carbon sphere structures with a diameter of approximately 250 nm.
[0069] from Figure 11 It can be seen that the nitrogen-doped carbon spheres described in this embodiment have a performance of 200 mAg. -1 At a current density, it exhibits a first-cycle coulombic efficiency of 33.1% and can cycle stably for 1000 cycles, with a reversible capacity of up to 505.8 mA hg after 1000 cycles. -1 .
[0070] Example 3
[0071] A nitrogen-doped carbon sphere is prepared by the following steps:
[0072] (1) Add 1.0 g of dopamine hydrochloride to a mixed solvent consisting of 1.5 mL ammonia, 80 mL ethanol and 180 mL deionized water. After stirring for 0.5 h, add 20 mL of deionized water and stir vigorously for 30 h to obtain a brown suspension.
[0073] (2) After centrifuging and washing the suspension, the solution is dried under vacuum at 80°C for 12 hours to obtain the precursor material.
[0074] (3) The precursor material is subjected to high-temperature heat treatment in an argon atmosphere. The specific heating program is as follows: the temperature is increased at a rate of 2℃ / min and held at 800℃ for 2h to obtain the nitrogen-doped carbon spheres.
[0075] The nitrogen-doped carbon spheres obtained in this embodiment were tested, and the scanning electron microscopy results are as follows: Figure 12 As shown, at 200mA g -1 Cyclic performance test results at current density are as follows Figure 13 As shown.
[0076] from Figure 12 As can be seen, the nitrogen-doped carbon spheres described in this embodiment are uniform nano-carbon sphere structures with a diameter of approximately 700 nm.
[0077] from Figure 13 It can be seen that the nitrogen-doped carbon spheres described in this embodiment have a performance of 200 mA g. -1At a current density, it exhibits a first-cycle coulombic efficiency of 50.2% and can cycle stably for 1000 cycles, with a reversible capacity of up to 212.5 mA hg after 1000 cycles. -1 .
[0078] Comparative Example 1
[0079] A nitrogen-doped hard carbon-coated silica spherical composite is prepared by the following steps:
[0080] (1) Add 1.0 g of dopamine hydrochloride to a mixed solvent consisting of 1.5 mL ammonia, 80 mL ethanol and 180 mL deionized water. After stirring for 0.5 h, add 1.5 mL of tetraethyl orthosilicate and 20 mL of deionized water. Stir vigorously for 30 h to obtain a suspension.
[0081] (2) After centrifuging and washing the suspension, the solution is dried under vacuum at 80°C for 12 hours to obtain the precursor material.
[0082] (3) The precursor material is subjected to high-temperature heat treatment in an argon atmosphere. The specific heating procedure is as follows: the temperature is increased at a rate of 5℃ / min and held at 1100℃ for 2h to obtain a spherical composite of nitrogen-doped hard carbon coated silicon dioxide.
[0083] The nitrogen-doped hard carbon-coated silica spherical composite obtained in this comparative example was tested, with the results measured at 200 mA g. -1 Cyclic performance test results at current density are as follows Figure 14 As shown. From Figure 14 It can be seen that the nitrogen-doped hard carbon-coated silica spherical composite described in this comparative example exhibits high performance at 200 mA g. -1 At the specified current density, the first-cycle coulombic efficiency is 26.3%, and the reversible capacity after 100 cycles reaches 14.6 mA hg. -1 .
[0084] Comparative Example 2
[0085] A nitrogen-doped hollow carbon sphere is prepared by the following steps:
[0086] (1) Add 1.0 g of dopamine hydrochloride to a mixed solvent consisting of 1.5 mL ammonia, 80 mL ethanol and 180 mL deionized water. After stirring for 0.5 h, add 1.5 mL of tetraethyl orthosilicate and 20 mL of deionized water. Stir vigorously for 30 h to obtain a suspension.
[0087] (2) After centrifuging and washing the suspension, the solution is dried under vacuum at 80°C for 12 hours to obtain the precursor material.
[0088] (3) The precursor material is subjected to high-temperature heat treatment in an argon atmosphere. The specific heating program is as follows: the temperature is increased at a rate of 5℃ / min and held at 1100℃ for 2h to obtain a spherical composite of nitrogen-doped hard carbon coated silicon dioxide.
[0089] (4) The nitrogen-doped hard carbon-coated silicon dioxide spherical composite was etched with 10% hydrofluoric acid, and after washing and drying, nitrogen-doped hollow carbon spheres were obtained.
[0090] The nitrogen-doped hollow carbon spheres obtained in this comparative example were tested, with the results measured at 200 mA g. -1 Cyclic performance test results at current density are as follows Figure 15 As shown. From Figure 15 It can be seen that the nitrogen-doped hollow carbon spheres described in this comparative example exhibit performance at 200 mAg. -1 At the given current density, the first-cycle coulombic efficiency is 81.5%, and the reversible capacity after 100 cycles reaches 112.8 mA hg. -1 .
[0091] The test results of Comparative Examples 1 and 2 show that the nitrogen-doped hard carbon-coated silica spherical composite and nitrogen-doped hollow carbon spheres obtained by adding tetraethyl orthosilicate have far inferior electrochemical performance as anode materials for sodium-ion batteries compared to the nitrogen-doped carbon nanospheres synthesized using this invention.
[0092] It should be noted that the above embodiments are only some embodiments of the present invention. The nitrogen-doped carbon spheres of the present invention prepared by changing parameters (dopamine hydrochloride dosage, composition and dosage of mixed solvent, polymerization reaction time, high temperature and time of high temperature heat treatment, etc.) through orthogonal experimental design methods all have wide carbon interlayer spacing, high electronic conductivity and fast sodium ion diffusion kinetics.
[0093] In summary, this invention can significantly increase the carbon interlayer spacing, sodium ion diffusion kinetics, and sodium storage active sites in hard carbon materials, achieving high capacity, long cycle life, and fast charge-discharge performance in hard carbon sodium storage anodes. Compared with existing technologies, this invention represents a significant advancement.
[0094] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes, and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. A method for preparing nitrogen-doped carbon spheres, characterized in that, Includes the following steps: S1: Add dopamine hydrochloride to the mixed solvent, stir for time T1, then add deionized water and continue stirring for time T2 until a brown suspension is obtained. S2: Centrifuge, wash and dry the suspension to obtain the precursor material; S3: The precursor material is subjected to high-temperature heat treatment under an inert atmosphere to obtain the nitrogen-doped carbon spheres.
2. The method for preparing nitrogen-doped carbon spheres according to claim 1, characterized in that, In step S1, the amount of dopamine hydrochloride used is 0.3 to 1.5 g, and the amount of the mixed solvent used is 220.5 to 324 mL.
3. The method for preparing nitrogen-doped carbon spheres according to claim 2, characterized in that, The mixed solvent includes 0.5–4 mL ammonia, 70–120 mL ethanol, and 150–200 mL deionized water.
4. The method for preparing nitrogen-doped carbon spheres according to claim 1, characterized in that, In step S1, the amount of deionized water used is 10-50 mL.
5. The method for preparing nitrogen-doped carbon spheres according to claim 1, characterized in that, In step S1, the time T1 is 0.5h, and the time T2 is 20 to 40h.
6. The method for preparing nitrogen-doped carbon spheres according to claim 1, characterized in that, In step S3, the inert atmosphere is argon and / or nitrogen.
7. The method for preparing nitrogen-doped carbon spheres according to claim 1, characterized in that, In step S3, the high-temperature heat treatment is carried out at a temperature of 500–2000℃ for 1–5 hours.
8. The method for preparing nitrogen-doped carbon spheres according to claim 7, characterized in that, In step S3, the heating rate used during high-temperature heat treatment is 2 to 10 °C / min.
9. A nitrogen-doped carbon sphere, characterized in that, It is prepared by the method for preparing nitrogen-doped carbon spheres according to any one of claims 1-8.
10. The application of nitrogen-doped carbon spheres as described in claim 9 as a negative electrode material for sodium-ion batteries.
Citation Information
Patent Citations
Mesoporous multilayer spiral chiral nitrogen-doped carbon nanosphere as well as preparation method and application thereof
CN115784206A
Preparation method and application of hollow spherical nitrogen-doped molybdenum carbide / carbon composite wave-absorbing material
CN116179156A
